CLINICAL SPECTRUM OF CIRRHOSIS LIVER A STUDY OF 167 CASES: Clinical Spectrum of Cirrhosis Liver - Aziz, Muhammad Shahid; Saed, Furrukh; Farooq, Muhammad (Pakistan Armed Forces Medical Journal, 2009)
Objective: The present study was designed to find out the aetiological pattern, presentation and to assess the severity of liver disease in patients of cirrhosis of at time of presentation. Study Design: A descriptive study. Place and Duration of Study: The study was conducted in the medical department of CMH Peshawar from January 2007 to June 2008. Patients and Method: This study was conducted in the Medical Department of Combined military hospital Nowshera and Combined military hospital Peshawar. Cirrhotic patients were admitted to Medical ward and necessary investigations were done. Serum was tested for Hepatitis B surface antigen (HBsAg) and antibodies against Hepatitis C virus (anti HCV) by ELISA method. Where negative, serum was tested for HBcAb (IgM as well as Total), Anti Nuclear antibody, Anti Smooth muscle antibody, Liver Kidney microsomal antibodies, serum Ferritin level, Transferrin saturation and serum ceruloplasmin level. Liver biopsy was done in selective cases. Results: Ninety-eight patients (58.6%) were male and sixty-nine (41.3%) were female.Out of 167 patients, 113 (67.6%) were found infected with HCV, 30 (17.9%) with HBV. In 18 patients (10.7%) all serological and metabolic profile was negative. Major presentations of Cirrhosis were coagulopathy (88%), Ascites (53.9%) , Anaemia (45.2%) and Jaundice (35.95%). 66 patients (39.5%) were in class A of Child-Pugh scoring system, 59 patients (35.3%) in class B and 42 patients (25%) in class C respectively. Conclusion: Cirrhosis liver due to HCV is more common than HBV in this region. Males are affected more than females. Majority of patients are in Child-Pugh class A and B at presentation.